2019
DOI: 10.12911/22998993/102966
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Productivity of a Roof-Type Solar Still Utilizing Alumina Nanoparticles and Vacuum Pump

Abstract: Unlike conventional fresh water producing systems, from saline or brackish water, the innovative solar water producing systems are efficient and effective. Experiments were conducted on two identical roof-type solar stills and simultaneously tested under the same weather conditions. One of these stills was modified by integrating a vacuum pump to lower the pressure inside while the other still was used as a reference unit. Different concentrations of Al 2 O 3 nanoparticles were chosen, 0.2%, 0.4%, and 0.6%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They showed that the use of energy storage increases productivity by 50% in the nocturnal period. In recent years, many researchers have investigated the effects of using various types of nanofluid on the performance of water purification solar still (Sahota & Tiwari 2016;Mutlq et al 2019;Parsa et al 2020;Singh et al 2020). Ajdari & Ameri (2022) evaluated the performance of an inclined stepped solar still integrated with phase-change materials PCM and a CuO/GO nanocomposite as a nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the use of energy storage increases productivity by 50% in the nocturnal period. In recent years, many researchers have investigated the effects of using various types of nanofluid on the performance of water purification solar still (Sahota & Tiwari 2016;Mutlq et al 2019;Parsa et al 2020;Singh et al 2020). Ajdari & Ameri (2022) evaluated the performance of an inclined stepped solar still integrated with phase-change materials PCM and a CuO/GO nanocomposite as a nanofluid.…”
Section: Introductionmentioning
confidence: 99%